Emergence of a novel subpopulation of CC398 Staphylococcus aureus infecting animals is a serious hazard for humans - van der Mee-Marquet, Nathalie L.; Corvaglia, Anna; Haenni, Marisa; Bertrand, Xavier; Franck, Jean-Baptiste; Kluytmans, Jan; Girard, Myriam; Quentin, Roland; François, Patrice (Frontiers in Microbiology, 2014)
Until recently, Staphylococcus aureus from clonal complex (CC)398 were mostly described as colonizing asymptomatic raised pigs and pig-farmers. Currently, the epidemiology of the CC398 lineage is becoming more complex. CC398 human-adapted isolates are increasingly being identified in bloodstream infections in humans living in animal-free environments. In addition, CC398 isolates are increasingly responsible for invasive infections in various animals. CC398 isolates that colonize asymptomatic pigs and the isolates that infect humans living in animal-free environments (human-adapted isolates) both lack several clinically important S. aureus–associated virulence factors but differ on the basis of their prophage content. Recent findings have provided insight into the influence of a φMR11-like helper prophage on the ability of CC398 isolates to infect humans. To assess the recent spread of the CC398 lineage to various animal species and to investigate the links between the φMR11-like prophage and the emergence of CC398 isolates infecting animals, we studied 277 isolates causing infections in unrelated animals. The prevalence of CC398 isolates increased significantly between 2007 and 2013 (p<0.001); 31.8 % of the animal isolates harbored the φMR11-like prophage. High-density DNA microarray experiments with 37 representative infected-animal isolates positive for φMR11-like DNA established that most infected-animal isolates carried many genetic elements related to antimicrobial resistance and virulence genes, and a φ3 prophage encoding immune-modulating proteins and associated with animal-to-human jumps. Our findings suggest recent clonal expansion and dissemination of a new subpopulation of CC398 isolates, responsible for invasive infections in various animals, with a considerable potential to colonize and infect humans, probably greater than that of human-adapted CC398 isolates, justifying active surveillance.